The Merits and Risks of AI-Assisted Academic Writing: Insights from Current Research - Silvana Neshkovska (ELOPE, 2025)
This paper explores the transformative role of Artificial Intelligence (AI) tools, specifically ChatGPT, in the acquisition of English as a foreign language. With the rapid evolution of educational technology, AI-driven chatbots like ChatGPT offer innovative methodologies to augment language teaching and learning. This study examines the potential of ChatGPT to improve English language students’ writing abilities by providing suggestions, corrections and automated assistance. Through a review of existing literature and a discussion of the findings of recent studies, the paper seeks to highlight the benefits and risks of integrating AI tools into language education, especially, in the context of writing. Insights gained from multiple studies suggest that while ChatGPT has the potential to significantly enhance language students’ writing skills in all phases of writing, by promoting engagement, motivation, and autonomy among learners, it also necessitates cautious use to ensure academic integrity and to prevent over-reliance, which in turn, can stifle students’ learning capacities.